ERP adoption factors: the effect of institutional- and economic-based theory - Kharuddin, Saira; Foong, Soon Yau; Senik, Rosmila (Universiti Putra Malaysia Press, 2013)
The introduction of the Enterprise Resource Planning (ERP) system in the early 1990s was perceived as a new way of managing a business that could lead to better management of an organisation and improve its efficiency. However, studies have repeatedly reported a low success rate in ERP system adoption. This encouraged various research studies that sought to uncover factors that could have contributed to the system failure. A poor decision-making process has been stated as one of the main reasons for ERP system failure. Clear objectives and good justification could, we believe, increase the ERP system adoption success rate. Hence, in this study, we extend the existing research on ERP by exploring the effect of institutional pressures and economic benefits on the decision-making process of the management. Specifically, we investigate the influence of external pressures and internal needs in ERP adoption decisions. Empirical analyses in this study are based on survey data obtained from 136 Malaysian companies. Overall, our findings indicate that only operational benefits and mimetic pressure have significant influence on ERP system adoption decisions. Other economic benefits such as managerial benefits and strategic benefits have no significant impact on the management’s decision to adopt the system. Similarly, institutional pressures, coercive pressures and normative pressures yield non-significant results. These results are important because the evidence highlights that the management’s decision to adopt the ERP system is based on the felt need for the organisation to improve its operational efficiency, and the influence of mimetic pressures further accentuates the importance for the organization of being competitive in its technological capabilities.